La relación entre el desarrollo de los municipios y la puntuaciónen Matemáticas: Un caso aplicado para Colombia; The relationship between the municipality development and mathematic score: The Colombian case - Jhon James Mora; Daniela Estrada Nates (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– This article analyzes the effect of the municipality on the academic result of the Colombian State test student "Saber 11". From linear hierarchical models with quantile regression, our results suggest that the type of municipality has a significant effect on students' academic achievement in mathematics for the quartiles studied. In this way, public policy makers must take into account the conditions of the place where students live when formulating educational policies aimed at improving educational quality, since this may affect inequality and opportunities to access higher education.
Keywords: A22; C31; 330; Saber 11 test; Multilevel quantile regressions; Mathematic score